Current approach to genetic testing and genetic evaluation referrals for adults with congenital heart disease - Oehlman, Laura B.; Opotowsky, Alexander R.; Weaver, Kathryn N.; Brown, Nicole M.; Barnett, Cara L.; Miller, Erin M.; He, Hua; Shikany, Amy R. (Frontiers in Genetics, 2024)
Background Congenital heart disease (CHD) is the most common congenital anomaly. Up to 33% have an identifiable genetic etiology. Improved medical and surgical management of CHD has translated into longer life expectancy and a rapidly growing population of adults living with CHD. The adult CHD (ACHD) population did not have access during childhood to the genetic technologies available today and therefore have not had a robust genetic evaluation that is currently recommended for infants with CHD. Given this potential benefit; the aims of this study were to determine how ACHD cardiologists offer genetics services to patients and identify the indications that influence decision-making for genetics care. Methods We performed a descriptive cross-sectional study of ACHD cardiologists. A studydeveloped questionnaire was distributed via emailed REDCap link. The recruitment email was sent to 104 potential respondents. The survey was open from 06/2022 to 01/2023. Results Thirty-five cardiologists participated in the study (response rate of 34%). Most cardiologists identified as white (77%) and male (66%). Cardiologists were more likely to refer patients to genetics (91%) than to order testing themselves (57%). Of the testing ordered, chromosomal testing (55%) was ordered more than gene sequencing (14%). Most cardiologists would refer a patient with a conotruncal lesion (interrupted aortic arch) over other indications for a genetics evaluation. There were more reported barriers to ordering genetic testing (66%) compared to referring to genetics for a genetics evaluation (23%). Cardiologists were more confident recognizing features suggestive of a genetic syndrome than ordering the correct test (p=0.001). Regarding associations between clinical factors and current practices, more years in practice trended towards less referrals and testing. Evaluating a greater number of patients (p=0.11) and greater confidence recognizing syndromic features (p=0.12) and ordering the correct test (p=0.09) were all associated with ordering more testing.Testing for microdeletion syndromes is being offered and completed in the ACHD population, however testing for single-gene disorders associated with CHD is being underutilized. Developing guidelines for genetic testing in adults with CHD could increase access to genetic services, impact medical management, reduce uncertainty regarding prognosis, and inform recurrence risk estimates.